Revolutions of Choice - Frank Barkow (Oz, 2011)
The invitation to contribute to this volume of the Oz journal reminds me that even though I am now Berlin-based, I was born in Kansas City (albeit on the Missouri side) and that I spent much time in my youth in Atchison, Kansas from where my parents come. During one of those hot humid summers, I worked as a carpenter with a local construction crew on a number of jobs up and down the river.